Carbohydrate mouth rinse improves morning high-intensity exercise performance - Clarke, N. L.; Hammond, S.; Kornilios, E.; Mundy, P. D. (European Journal of Sport Science, 2017)
Oral carbohydrate (CHO) rinsing has been demonstrated to provide beneficial effects on exercise performance of durations of up to one hour. The aim of the present study was to investigate the effects of CHO mouth rinsing on morning high-intensity exercise performance. Following institutional ethical approval and familiarisation, 12 healthy males (mean±SD age: 23±3 years, height: 175.5±7.4 cm, body mass: 75.4±7.5 kg) participated in this study. Countermovement jump (CMJ) height, isometric mid-thigh pull peak force, 10 m sprint time and bench press and back squat repetitions to failure were assessed following CHO and placebo (PLA) rinsing or a control condition (CON). All testing took place at 07:30 following an 11 hour overnight fast. Performance of CMJ height (CHO: 39 ± 7 cm; PLA: 38 ± 7 cm; CON: 36 ± 6 cm; P =.003, =0.40), 10 m sprint time (CHO: 1.78 ± 0.07 s; PLA: 1.81 ± 0.07 s; CON: 1.85 ± 0.05 s; P = .001, = 0.47), the number of bench press (CHO: 25 ± 3; PLA: 24 ± 4; CON: 22 ± 4; P < 001, =?0.55) and squat (CHO: 31 ± 4; PLA: 29 ± 5; CON: 26 ± 6; P <.001, =0.70) repetitions and mean felt arousal (CHO: 5±1; PLA: 4±0; CON: 4±0; P=.009, =?0.25) improved following CHO rinsing. However, isometric mid-thigh pull peak force was unchanged (CHO: 2262±288 N; PLA: 2236± 354 N; CON: 2212±321 N; P=.368, =0.08). These results suggest that oral CHO rinsing solution significantly improved the morning performance of CMJ height, 10 m sprint times, bench press and squat repetitions to failure and felt arousal, although peak force during an isometric mid-thigh pull, rating of perceived exertion and heart rate were unaffected.